2024
DOI: 10.1039/d3lp00085k
|View full text |Cite
|
Sign up to set email alerts
|

How introduction of hydrolyzable moieties in POx influences particle formation – a library approach based on block copolymers comprising polyesters

Natalie E. Göppert,
Antje Vollrath,
Leanne M. Stafast
et al.

Abstract: A library of fully degradable amphiphilic block copolymers based on degradable polyoxazoline analogues and polyesters synthesized via strain-promoted azide–alkyne cycloaddition was used to obtain particle formulations in a high-throughput approach.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 35 publications
0
3
0
Order By: Relevance
“…The large structural diversity of the POx backbone gives a clear incentive for the development of nanomedicine applications, on the condition that heterotelechelics can be obtained with high end‐group fidelity, conform to heterotelechelic PEGs. Previous studies, however, have shown the presence of H‐initiated species, typically seen in MALDI‐TOF‐MS spectra, [21,22,39,40] which compromise the end‐group fidelity on the α‐end. These H‐initiated species arise due to chain transfer reactions over the course of the CROP, either via intrinsic chain transfer, i.e.…”
Section: Resultsmentioning
confidence: 98%
“…The large structural diversity of the POx backbone gives a clear incentive for the development of nanomedicine applications, on the condition that heterotelechelics can be obtained with high end‐group fidelity, conform to heterotelechelic PEGs. Previous studies, however, have shown the presence of H‐initiated species, typically seen in MALDI‐TOF‐MS spectra, [21,22,39,40] which compromise the end‐group fidelity on the α‐end. These H‐initiated species arise due to chain transfer reactions over the course of the CROP, either via intrinsic chain transfer, i.e.…”
Section: Resultsmentioning
confidence: 98%
“…PEtOx-N 3 was synthesized as described in our recent publication . MeOTs (2.269 mL, 2.800 g, 15.03 mmol) and EtOx (61 mL, 60 g, 0.61 mol, 41 equiv) were dissolved in dry acetonitrile (87 mL) under an argon atmosphere in a predried flask, corresponding to a [monomer]-to-[initiator] ratio [M]/[I] of 40:1 and a monomer concentration of 4 M. Subsequent to stirring for 7 h at 80 °C, NaN 3 (4.9 g, 75 mmol, 5.0 equiv) was added and the reaction mixture was stirred for an additional 14 h at 70 °C.…”
Section: Methodsmentioning
confidence: 99%
“…The large structural diversity of the POx backbone gives a clear incentive for the development of nanomedicine applications, on the condition that heterotelechelics can be obtained with high end-group fidelity, conform to heterotelechelic PEGs. Previous studies, however, have shown the presence of H-initiated species, typically seen in MALDI-TOF-MS spectra, [21,22,39,40] which compromise the end-group fidelity on the α-end. These H-initiated species arise due to chain transfer reactions over the course of the CROP, either via intrinsic chain transfer, i.e.…”
Section: Reactive Heterotelechelic Poxmentioning
confidence: 97%